A New Weighted Half-Logistic Distribution:Properties, Applications and Different Method of Estimations - Hashempour, Majid; Alizadeh, Morad (Statistics, Optimization & Information Computing, 2023)
In this paper, we introduce a new two-parameter lifetime distribution based on arctan function which is called weighted Half-Logistic (WHL) distribution. Theoretical properties of this model including quantile function, extreme value, linear combination for pdf and cdf, moments, conditional moments, moment generating function and mean deviation are derived and studied in details. The maximum likelihood estimates of parameters are compared with various methods of estimations by conducting a simulation study. Finally, two real data sets show that this model p[rovide better fit than other competitive known models.